Analyzing injury patterns in climbing: a comprehensive study of risk factors - Kovárová, M.; Pyszko, P.; Kikalová, K. (Sports, 2024)
Climbing, a sport with increasing popularity, poses diverse risks and injury patterns across its various disciplines. This study evaluates the incidence and nature of climbing-related injuries, focusing on how different disciplines and climbers` personal characteristics affect these injuries. Data on injury incidence, severity, and consequences, as well as climbers` personal attributes, were collected through a questionnaire and analyzed using generalized linear models and generalized linear mixed models, Cochran-Armitage tests, and multivariate analysis. Our findings indicate a direct correlation between time spent on bouldering and lead climbing and increased injury frequency, while injury incidence decreases with time in traditional climbing. Interestingly, personal characteristics showed no significant impact on injury incidence or severity. However, distinct patterns emerged in individual disciplines regarding the recent injuries in which age and weight of climbers play a role. While the phase of occurrence and duration of consequences show no significant variation across disciplines, the intensity of the required treatment and causes of injury differ. This research provides insights into climbing injuries` complex nature, highlighting the need for tailored preventive strategies across climbing disciplines. It underscores the necessity for further investigation into the factors contributing to climbing injuries, advocating for more targeted injury prevention and safety measures in this evolving sport.